Extracellular Matrix-regulated Gene Expression Requires Cooperation of SWI/SNF and Transcription Factors - Xu, Ren; Spencer, Virginia A.; Bissell, Mina J. (The Journal of biological chemistry, 2007)
Extracellular cues play crucial roles in the transcriptional regulation of tissue-specific genes, but whether and how these signals lead to chromatin remodeling is not understood and subject to debate. Using chromatin immunoprecipitation assays and mammary-specific genes as models, we show here that extracellular matrix molecules and prolactin cooperate to induce histone acetylation and binding of transcription factors and the SWI/SNF complex to the β- and γ-casein promoters. Introduction of a dominant negative Brg1, an ATPase subunit of SWI/SNF complex, significantly reduced both β- and γ-casein expression, suggesting that SWI/SNF-dependent chromatin remodeling is required for transcription of mammary-specific genes. Chromatin immunoprecipitation analyses demonstrated that the ATPase activity of SWI/SNF is necessary for recruitment of RNA transcriptional machinery, but not for binding of transcription factors or for histone acetylation. Co-immunoprecipitation analyses showed that the SWI/SNF complex is associated with STAT5, CCAAT/enhancer-binding protein β, and glucocorticoid receptor. Thus, extracellular matrix- and prolactin-regulated transcription of the mammary-specific casein genes requires the concerted action of chromatin remodeling enzymes and transcription factors.